Financial management tools in the tasks of ensuring the competitiveness of livestock products (Economics and region, 2022)
One of the decisive factors of commercial success of the company is budgeting, as it helps managers responsible for a particular business process to clearly understand and perform their tasks. It also helps to assess opportunities and plan their achievement in time, make necessary adjustments, develop a resource plan of the company. In the current economic conditions, it is extremely important for enterprises to predict critical situations for successful functioning. Producers and entrepreneurs should proactively approach the issues of quality and safety of products, because when problems arise, they have serious negative consequences for the respective enterprise. The purpose of this study is to evaluate and determine the procedure and mechanism for applying budgeting tools at livestock enterprises and improving competitiveness. In today's rather difficult economic realities, companies are looking for the most effective ways to control the results of the company's activities to carry out business activities. For a successful "game" in the market, companies that are trying to succeed in the fight against their competitors by legal methods need to have their own strategic development plan, which reflects the goals, objectives of the company's development and ways to achieve them, taking into account possible scenarios of deviation from the plan. Budgeting also serves to overcome these unpredictable factors as painlessly as possible. Information about the state of budgets gives the company's management the opportunity to analyze the financial results of the company's structural units, to identify promising areas of activity, as well as areas for differentiation of activities or structural reorganization (curtailment of one type of activity and development of another). Today, budgeting is a key tool of modern management, which contributes to improving the efficiency of the company. Using budgeting tools, managers are able to more fully control the activities of all structural units of the organization, promote their effective interaction and direct them to achieve common strategic goals. At the same time, budgeting makes it possible to predict and assess potential risks and, accordingly, promptly take the necessary measures.
Keywords: competitiveness; livestock products; budgeting; planning; financial management